2017
DOI: 10.1099/jmm.0.000512
|View full text |Cite
|
Sign up to set email alerts
|

Effect of involved Aspergillus species on galactomannan in bronchoalveolar lavage of patients with invasive aspergillosis

Abstract: Purpose. The detection of galactomannan (GM) in bronchoalveolar lavage (BAL) fluid is an important surrogate marker for the early diagnosis and therapeutic monitoring of invasive aspergillosis (IA), regardless of the involved species of Aspergillus. Here, we utilized the Platelia Aspergillus GM enzyme immunoassay (Bio-Rad) to evaluate the GM index in BAL fluid samples from patients with proven, probable or putative IA due to Aspergillusflavus versus Aspergillusfumigatus.Methodology. In a prospective study betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 60 publications
0
16
0
Order By: Relevance
“…Combining nucleic acid tests with galactomannan can hasten diagnosis and improve clinical outcomes in some populations [48][49][50][51]; further, incorporation of immune function may also improve discrimination of colonization and invasive mycosis [52][53][54][55][56]. Importantly, for all nucleic acid-based tests, measurable Aspergillus yield varies among species and according to life stage, cell wall characteristics, and hydrophobicity [57]. Therefore, any future clinical mNGS assay will need to be benchmarked against numerous Aspergillus species as well as other medically relevant fungi in order to have the broadest utility.…”
Section: Discussionmentioning
confidence: 99%
“…Combining nucleic acid tests with galactomannan can hasten diagnosis and improve clinical outcomes in some populations [48][49][50][51]; further, incorporation of immune function may also improve discrimination of colonization and invasive mycosis [52][53][54][55][56]. Importantly, for all nucleic acid-based tests, measurable Aspergillus yield varies among species and according to life stage, cell wall characteristics, and hydrophobicity [57]. Therefore, any future clinical mNGS assay will need to be benchmarked against numerous Aspergillus species as well as other medically relevant fungi in order to have the broadest utility.…”
Section: Discussionmentioning
confidence: 99%
“…In a study of hematologic malignancy patients by Hachem et al, the sensitivity of serum GM was higher with aspergillosis due to non- fumigatus Aspergillus species (49%) than those infected with A. fumigatus (13%), though non- fumigatus Aspergillus species were not specified in the study [55]. The mean BAL-GM index in pulmonary aspergillosis patients with A. flavus (GM Index 1.6) was lower than A. fumigatus (3.1; P = 0.031) and the sensitivity of GM detection was lower in A. flavus infections [56]. A study conducted by Badiee et al in children with IA demonstrated sensitivity and specificity of GM, (1→3)-β- d -glucan and PCR was 90% and 92%, 50% and 46%, and 80% and 96%, respectively [57].…”
Section: Diagnosismentioning
confidence: 99%
“…In tropical and subtropical countries of the Middle-East, such as Iran, species of Aspergillus section Flavi are reportedly the main aetiological agents of invasive and non-invasive infections. 3,4 The taxonomy of this section is complex and is currently under development. 5 A large number of species in section Flavi are commonly observed plant pathogens producing several mycotoxins.…”
Section: Amongmentioning
confidence: 99%